A qualitative descriptive study exploring the perception of confidence within midwives facilitating water birth in Western Australia - Nicholls, Sarah Louise (Curtin University, 2014)
This qualitative study explored midwives' perceptions of 'becoming and being confident' in supporting water birth. Twenty six midwives participated. Three categories emerged: What came before the journey describes influences prior to initial exposure such as education and personal attitudes. Becoming confident – the journey offers insight into the impact of another midwife in the room, getting enough exposure and 'unlearning' ingrained practices. Staying confident highlights factors that ‘knock’ confidence plus empowering experiences that sustained confidence.